Study of the decay B̄0→D*+ωπ- - Aubert, B; Barate, R; Bona, M; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges, E; Palano, A; et al. (2006)
We report on a study of the decay B̄0→D*+ωπ- with the BABAR detector at the PEP-II B-factory at the Stanford Linear Accelerator Center. Based on a sample of 232×106 BB̄ decays, we measure the branching fraction B(B̄0→D*+ωπ-)=(2.88±0. 21(stat.)±0.31(syst.))×10-3. We study the invariant mass spectrum of the ωπ- system in this decay. This spectrum is in good agreement with expectations based on factorization and the measured spectrum in τ-→ωπ-ντ. We also measure the polarization of the D*+ as a function of the ωπ- mass. In the mass region 1.1 to 1.9 GeV we measure the fraction of longitudinal polarization of the D*+ to be ΓL/Γ=0.654±0.042(stat.)±0.016(syst.). This is in agreement with the expectations from heavy-quark effective theory and factorization assuming that the decay proceeds as B̄0→ D*+ρ(1450)-, ρ(1450)-→ωπ-. © 2006 The American Physical Society.